Orthopedic Trauma Epidemiology in Pediatric Patients at a Tertiary Care Trauma Center in North India - Syed Faisal Afaque; Vikas Verma; Farhat Fatima; Ajai Singh (Journal of Orthopedics, Traumatology and Rehabilitation)
Introduction: In North India, orthopedic trauma, which refers to injuries affecting the bones, joints, and soft tissues, occurs frequently in pediatric patients. The aim of this study is to investigate the epidemiology, etiology, mechanisms of injury, and outcomes of orthopedic trauma in pediatric patients who are admitted to a tertiary care trauma center located in North India. Materials and Methods: This prospective study was carried out over 1 year between January 2019 and December 2019, which included 479 pediatric orthopedic trauma patients between the age group of 0 and 18 years. The collected data were systematically classified and analyzed with respect to the mode of trauma, type of injury, and outcome across various age groups and genders. Results: Age of children ranged from 0 to 18 years, of which 298 (62.2%) were male and 181 (37.8%) were female. Most fractures occurred at aged 9–12 years (38.4%) and the trend decreased with age. Fall injuries were the most common mode of trauma (49.9%, n = 239) followed by road traffic accident (29.4%, n = 141). Among operated patients, most injuries were closed (47.2%, n = 138) followed by compound injuries (32.2%, n = 94) and crush injuries (20.6%, n = 60). Sixty-three percentage of patients recovered well with independent functional status, while 30% recovered with supported functional status/residual deformity. Conclusion: Orthopedic trauma in pediatric population is growing up and prehospital care is lagging which is more required than adult counterpart. An effective and aggressive management of accident prevention programme is required, which should also include changes in lifestyle and environment, overcoming obstacles such as ignorance, inadequate resources, and illiteracy.